2013
DOI: 10.1007/s10903-013-9921-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Topography in Korean American and White Men: Preliminary Findings

Abstract: Introduction This is the first study of Korean Americans’ smoking behavior using a topography device. Korean American men smoke at higher rates than the general U.S. population. Methods Korean American and White men were compared based on standard tobacco assessment and smoking topography measures. They smoked their preferred brand of cigarettes ad libitum with a portable smoking topography device for 24 hours. Results Compared to White men (N = 26), Korean American men (N = 27) were more likely to smoke l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The outcome of our study demonstrated similar puff volumes, puff durations, average puff flow rates, and peak flow rates as those obtained from US-dwelling Korean immigrants and American citizens who used the same type of topograph measuring device. However, it also demonstrated that Korean smokers tended to smoke much intensively; the interpuff interval of 8.9 s among Koreans participating in our study was much shorter than that of Americans (25 s) or Korean immigrants living in the USA (13.5 s) [ 8 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The outcome of our study demonstrated similar puff volumes, puff durations, average puff flow rates, and peak flow rates as those obtained from US-dwelling Korean immigrants and American citizens who used the same type of topograph measuring device. However, it also demonstrated that Korean smokers tended to smoke much intensively; the interpuff interval of 8.9 s among Koreans participating in our study was much shorter than that of Americans (25 s) or Korean immigrants living in the USA (13.5 s) [ 8 ].…”
Section: Discussionmentioning
confidence: 97%
“…An interviewer-administered questionnaire was used to collect information about demographic characteristics (e.g., age, sex, education level, and race/ethnicity), smoking behaviors (self-reported smoking status, daily smoking amount, nicotine dependence based on the Fagerstrom score, cigarette brand name, number of packages smoked daily), and socioeconomic status. A clinical Research Support System (CReSS) pocket device (BORGWALDT, Richmond, VA, USA) was used to collect data containing the distributions of puff volumes, puff durations, and interpuff intervals from cigarette smoking during a 24-hour period, which was used in many previous studies as a valid tool [ 6 , 7 , 8 ]. Urine samples were collected from participants who completed topography analyses and were subjected to measurements of cotinine, OH-cotinine, and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) concentrations using liquid chromatography-tandem mass spectrometry [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking topography studies provide useful information on the relationship between smoking behavior and smoking cessation, and topography has been measured in settings outside of the laboratory. Prior work has examined smoking topography in the real world to determine differences in smoking patterns among groups of people (e.g., chippers vs dependent smokers; Brauer, 1996; Korean American vs White men; Chung, Kim, Kini, Fang, Kalman, & Ziedonis, 2015). Research has also shown that self-reported cigarettes smoked per day were not associated with smoking topography patterns in day-to-day life (Hatsukami, Morgan, & Pickens, 1987).…”
Section: Smoking Topography and Carbon Monoxidementioning
confidence: 99%
“…For example, based on the 2009 to 2011 Risk Factor Survey, 36% of Korean men and 11% of Korean women in New York City were smokers, whereas the rates were 19% and 4% for all Asian men and women, respectively, and 14% for the whole city population (Li et al, 2013). Although Korean men smoked fewer cigarettes, they did with greater puff-flows and much shorter intervals than White men (Chung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%